Batang Arau River Analysis As New Potential Original Local Government Revenue Of Padang City-Indonesia - Suryani, Yosi; Rinaldy, Rudy (International Journal of Educational Research & Social Sciences, 2022)
This study aims to analyze the Batang Arau River as one of the potential sources of Padang City's new Original Local Government Revenue from 2017-2021 how much is the projected potential OLGR generated in 2022 as other legitimate OLGR other income. Primary data sources are observations and interviews with the Padang City Regional Revenue Agency and the community around the Batang Arau River. Secondary data was obtained from BPS in 2021. The formula for processing data is the reference of Syafruddin (2002), which compares the realization of levy receipts for ships anchored in the Batang Arau River with the realization of regional revenues, multiplied by 100%.The results showed an increase in Padang City OLGR in 2017: 0.23%, 2018: 0.18%, 2019: 0.23%, 2020: 0.22% and in 2021: 0.25% of the realized value OLGR achieved. The average percentage increase in OLGR over five years is 0.22%. The projected addition of OLGR in 2022 is 0.18% of the PAD target to be achieved. It can be concluded that this area can be a potential source of new OLGR by attracting a levy on ships on the river. The difference between this article and the previous one is that it is found that the projection of the level of income obtained from boat activities on the Batang Arau River for 2022 is found, while the previous article analyzed PAD from 17 sectors as a source of regional income.